Genocide, collective violence, and popular memory : the politics of remembrance in the twentieth century - Lorey, David E.; Beezley, William H. (World beat series, 2002)
In Genocide, Collective Violence, and Popular Memory: The Politics of Remembrance in the Twentieth Century, the editors present and discuss the many different social responses to the challenge of coming to terms with past reigns of terror and collective violence. Designed for undergraduate courses in political violence and revolution, this volume treats a wide variety of incidents of collective violence-from decades-long genocide to short-lived massacres. The selection of essays provides a broad range of thought-provoking case studies from Latin America, Africa, Europe, and Asia. This provocat.